MECHANICAL PROPERTIES OF STEEL AISI 1045 VARIATION OF AUSTENITIZATION HOLDING TIME IN THE QUENCHING-TEMPERING PROCESS WITH ICE WATER MEDIA - Parmita, Ade Yusariarta Putra; Utomo, Yogi Mirza Pangestu; Rakhmat, Arie Mifthahul; Lubis, Muthia Putri Darsini (Jurnal Rekayasa Mesin, 2024)
AISI 1045, Medium-carbon steel is commonly used as machining components like bulldozer bushings and widely used in construction equipment such as hammerheads. Hence, it needs good hardness and impact resistance. The methods to achieve these properties are through a heat treatment process called quenching and tempering. This research analyzed the effects of various austenitizing holding times during the quenching and tempering process on the microstructure, hardness, and impact strength of AISI 1045 steel. The procedure involved quenching the steel at a temperature of 850°C with austenitizing holding times of 5, 15, and 25 minutes, followed by rapid cooling using ice water. Subsequently, tempering was performed at 500°C with a holding time of 15 minutes, followed by air cooling. The research showed that all three test specimens exhibited bainite and martensite phases. The hardness of the steel increased after undergoing the quenching and tempering process, with the highest hardness value obtained at a 5-minute austenitizing holding time, measuring 32.37 HRC. Additionally, there was an increase in impact strength after the quenching and tempering process. Tobe found the highest impact strength value observed at with a 25-minute austenitizing holding time at 27.39 J/cm².